Enhancing the critical role of Malaysian institute of higher education from Ivy League American universities research culture experiences - Jusoff, Kamaruzaman; Abu Samah, Siti Akmar; Abdullah, Zaini (Canadian Center of Science and Education, 2009)
Emulation by example is an old adage that has been a pragmatic initiative in great endeavors. To create a dynamic research culture too requires revisiting eminent personality and renowned organization by which one can copy in order to establish credibility. This paper explores the practicality of the emulation activities that help to establish this dynamic research culture. Here, the writers address the American Ivy League universities as the exemplary institutions of knowledge that have been long established and that Malaysian institutions of higher education can continue to learn and adapt in order to continue achieving academic excellence, particularly in research practices. Pertinent areas covered are the current research and innovation taking place in the US tertiary education, nurturing academic entrepreneurship, the need for effective research leaders, creating talent pool for researchers’ succession planning and internationalization, just to state a few. Simultaneously, establishing the research infrastructure and capacity is also another exploration that provides insights into the pertinent scope of academic establishment. This needs undivided attention by the leadership in the university. Through this sharing which is part of the experience acquired by the first author being an associate of an Ivy League institution, invaluable information in the paper can assist readers in understanding what is needed to establish a dynamic research culture for tertiary community.